2020
DOI: 10.4037/ajcc2020831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workplace Climate on Burnout Among Critical Care Nurses in the Veterans Health Administration

Abstract: Background Burnout is a maladaptive response to work-related stress that is associated with negative consequences for patients, clinicians, and the health care system. Critical care nurses are at especially high risk for burnout. Previous studies of burnout have used survey methods that simultaneously measure risk factors and outcomes of burnout, potentially introducing common method bias. Objectives To evaluate the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Fifth, previous studies revealed the presence of considerable differences across different hospitals, identifying hospital-level perceptions of workplace climate as the strongest antecedent of health outcomes [ 81 ]. Thus, healthcare professionals working in the same hospital would be more similar with regards to their perceptions of ethical climate and moral distress [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, previous studies revealed the presence of considerable differences across different hospitals, identifying hospital-level perceptions of workplace climate as the strongest antecedent of health outcomes [ 81 ]. Thus, healthcare professionals working in the same hospital would be more similar with regards to their perceptions of ethical climate and moral distress [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“… 18 One factor found to contribute to employee decision to leave their jobs in healthcare settings is their perception of an unsafe working environment. 19 Such feeling is well enhanced with the chaos that has been witnessed during the few months of the outbreak of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Although strategies targeting the support.....self harm, burnout is commonly fueled by systemic problems at the workplace necessitating more comprehensive interventions at the organization level. As mentioned earlier, chaotic work environment, disorganized workflow, lack of support and respect of individuals’ identities, and the pressure to deliver more with less support are all workplace‐related factors of which the employees often have no control 32–35 . Lack of knowledge, poor management, workplace discrimination, unwillingness to acknowledge burnout, complacency, or lack of empathy from the administrators and the leadership teams are all potential contributing factors to accelerate or amplify burnout.…”
Section: Peoplementioning
confidence: 99%
“…As mentioned earlier, chaotic work environment, disorganized workflow, lack of support and respect of individuals' identities, and the pressure to deliver more with less support are all workplace-related factors of which the employees often have no control. [32][33][34][35] Lack of knowledge, poor management, workplace discrimination, unwillingness to acknowledge burnout, complacency, or lack of empathy from the administrators and the leadership teams are all potential contributing factors to accelerate or amplify burnout. Asking workers to meditate or join a yoga class will not fully address the problem.…”
Section: Theme 1: People-centered Professional Development In the Futurementioning
confidence: 99%